2021
DOI: 10.4149/neo_2020_200506n494
|View full text |Cite
|
Sign up to set email alerts
|

Novel spectroscopic biomarkers are applicable in non-invasive early detection and staging classification of colorectal cancer

Abstract: awareness of physical examination or the limitations of an early diagnostic level. Despite the improving standard of modern medicine, mortality from CRC is still remarkably high and the prognosis remains poor in many cases because of disease detection at advanced clinical stages. Raman spectroscopy yields precise information, not only regarding the secondary structure of proteins but also regarding the discrimination between normal and malignant tissues. We investigated whether this method can be used for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This gap in knowledge also raises concerns about the reliability of their findings. Moreover, it was also observed that combining FTIR spectroscopy with other conventional spectroscopies or integrating machine learning models can improve diagnostic accuracy for CRC [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gap in knowledge also raises concerns about the reliability of their findings. Moreover, it was also observed that combining FTIR spectroscopy with other conventional spectroscopies or integrating machine learning models can improve diagnostic accuracy for CRC [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were included in our analysis. One study [17] analyzed 63 plasma specimens from CRC cases (n=30) and healthy controls (n=33) using ATR-FTIR.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Distinguishing between benign and malignant polyps can be achieved via spectroscopic visualization of their histological characteristics, including tissue [7,22,23] and subcellular [24] structures. Moreover, non-invasive analysis of the blood serum [15,25], blood plasma [26,27], or isolated serum proteins [28,29] by chiroptical and vibrational spectroscopy could also help in the early detection of this disease.…”
Section: Introductionmentioning
confidence: 99%